investigation of bovine tuberculosis in a private cattle herd in south-western Nigeria: potential riskss for human infection. (2014)
Introduction. Food-borne disease outbreaks remain a major global health challenge and cross-contamination from raw meat due to poor handling is a major cause in developing countries. Adequate knowledge of meat handlers is important in limiting these outbreaks. This study evaluated and compared the safe meat-handling knowledge, attitudes and practices (KAP) of private (PMPP) and government meat processing plants’ (GMPP) workers in south-western Nigeria. Methods. This cross sectional study comprised 190 meat handlers (PMPP = 55; GMPP = 135). Data concerning their safe meat-handling knowledge, attitudes and practices as well as their socio-demographic characteristics, such as age, gender and work experience were collected. Results. A significant association was observed between the type of meat processing plants and their knowledge (p = 0.000), attitudes (p = 0.000) and practices (p = 0.000) of safe meat-handling. Meat handlers in the GMPP were respectively, about 17 times (OR = 0.060, 95%CI: 0.018-0.203), 57 times (OR = 0.019, 95% CI: 0.007-0.054) and 111 times (OR = 0.009, 95%CI: 0.001- 0.067) less likely to obtain good knowledge, attitude and practice level of safe meat-handling than those from PMPP. Further, KAP levels were significantly associated with age group, education and work experience (p < 0.05). Discussion. Study findings suggest the need for future policy in food industry in developing countries to accommodate increased involvement of private sector for improved food safety and quality delivery. Public health education on safe food handling and hygiene should be on the front burner among food handlers in general.